Deforestation Trends in the Congo Basin : Mining - Hund, Kirsten; Megevand, Carole; Gomes, Edilene Pereira; Miranda, Marta; Reed, Erik (World Bank, Washington, DC, 2014)
This report aims at providing stakeholders with a good analysis of the potential impacts of mining development on the Congo Basin forests. It is one of a series of outputs prepared during a two-year exercise to analyze and better understand the deforestation dynamics in the Basin. It presents the main findings of an analysis of the mining potential in the Congo Basin as well as the global trends in demand of minerals tries to identify ways to reconcile mining development and preservation of the Congo Basin forests. It is based on an in depth analysis of the sector. The report is structured as follows: first chapter gives an overview of the mineral wealth in the Congo Basin; second chapter analyses the prospects for mining development in the Congo Basin; Third chapter assesses the potential impact of mining developments on forests; and the last chapter tries to identify ways to reconcile mining development and preservation of the Congo Basin forests.